Multiple HIV-1/M + HIV-1/O dual infections and new HIV-1/MO inter-group recombinant forms detected in Cameroon. Issue 1 (December 2017) - Oliveira, Fabienne; Mourez, Thomas; Vessiere, Aurélia; Ngoupo, Paul-Alain; Alessandri-Gradt, Elodie; Simon, François; Rousset, Dominique; Plantier, Jean-Christophe
Abstract Background Due to the prevalence of HIV-1 group M and the endemicity of HIV-1 group O infections in Cameroon, patients may be infected with both viruses and/or with HIV-1/MO recombinant forms. Such atypical infections may be deleterious in terms of diagnosis and therapeutic management due to the high divergence of HIV-1/O. The aim of this study was to identify prospectively such atypical infections in Cameroon. Results Based on serological screening byenv -V3 serotyping and a molecular strategy using group-specific (RT)-PCRs, we identified 10 Cameroonian patients harboring three different profiles of infection: (1) 4 HIV-1/M + O dual infections without evidence of recombinant; (2) 5 recombinants associated with one or both parental strains; and (3) 1 new recombinant form without parental strains. Conclusions This work highlights the dynamic co-evolution of these two HIV groups in Cameroon that could lead to the emergence of a circulating recombinant form MO, and the need for accurate identification of such atypical infections for precise diagnosis, virological monitoring and therapeutic management with adapted tools.